Ion beam-induced modification of structural and optical properties of MgTiO3 nanocrystalline thin films. Issue 1 (1st February 2017) - Vinod, Arun; Rathore, Mahendra Singh; Santhosh Kumar, T.; Pamu, D.; Pathak, A. P.; Srinivasa Rao, N.
ABSTRACT: MgTiO3 thin films were deposited on an amorphous silicon dioxide substrate by the RF magnetron sputtering method by varying the argon and oxygen mixing percentage. These pristine thin films were subjected to thermal annealing at a temperature of 700°C and subsequently two sets of crystalline thin films were irradiated using 100 MeV Au 8+ ions at a fixed fluence of 2 × 10 13  ions/cm 2 . XRD spectra reveal that the crystallite size reduces from 21 to 15 nm and crystallinity also decreases drastically after irradiation. AFM images show significant variation in the surface morphology upon irradiation. Optical studies suggest that the band gap as well as the refractive index are both reduced due to SHI irradiation. Ion beam induced modification of the structural, morphological and optical properties of MgTiO3 thin films and the possible mechanisms responsible for variation of the properties of MgTiO3 due to swift heavy ion beam irradiation have been discussed in detail.